Effect of Magnetocrystalline Anisotropy on the Magnetic Properties of Electrodeposited Co–Pt Nanowires - Escrig-Murua, J; Espejo-Pina, A (Kluwer Academic Publishers, 2014)
We report on the influence of the magnetocrystalline anisotropy on the easy magnetization axis, magnetization reversal and magnetic domain configurations of electrodeposited Co–Pt nanowires with lengths in the range of 4–6 µm and a diameter of 250 nm. The transmission electron microscopy and the X-ray diffractions revealed that the nanowires are composed of an intermixture of hcp- and fcc-textured crystal structures. The crystallographic orientations of both phases were such that the [001¯] of the hcp phase and the [111] of the fcc phase are pointing almost perpendicular to the nanowire axis. This observation allows us to understand the perpendicular easy magnetization axis of the nanowire arrays measured with vibrating sample magnetometry. Analytical calculations of the angular dependence of the coercivity revealed that the magnetization reversal changes from vortex to transverse mode at the applied field angle ? = 30°. Fitting of the experiment to these calculations results in a perpendicular effective anisotropy constant (Keff = 2.6 × 104 J/m3) in nanowires which can be ascribed to the strong magnetocrystalline anisotropy. Furthermore, the magnetic domain configurations of individual nanowires of length range 4 < L < 6 µm are studied using magnetic force microscopy. This reveals a spatial magnetization modulation along the length of the nanowires, which was found to be length dependent. Such an intrinsic modulation is attributed to the competition between the magnetocrystalline anisotropy and the shape anisotropy in the nanowires. We believe that this interplay between anisotropies gives rise to a magnetic configuration involving vortex-like structure with alternating chirality along the length of the nanowires. © 2014, Springer Science+Business Media Dordrecht.